Development of Deltamethrin-Laced Attractive Toxic Sugar Bait to Control Aedes aegypti (Linnaeus) Population - Sarita Kumar; Aarti Sharma; Roopa Rani Samal; Vaishali Verma; Ravinder Kumar Sagar; Shri Pati Singh; Kamaraju Raghavendra (Journal of Tropical Medicine, 2024)
Background. The attractive toxic sugar bait (ATSB) is a promising strategy for controlling mosquitoes at the adult stage. The strategy is based on the use of a combination of fruit juice, sugar, and a toxin in order to attract and kill the adult mosquitoes. The selection of the components and optimization of their concentrations is significant for the formulation of an effective ATSB. Methods. The present study formulated nine ATSBs and evaluated their efficacy against two laboratory strains (AND-Aedes aegypti and AND-Aedes aegypti-DL10) and two wildcaught colonized strains of Aedes aegypti (GVD-Delhi and SHD-Delhi). Initially, nine attractive sugar baits (ASBs) were prepared using a mixture of 100% fermented guava juice (attractant) with 10% sucrose solution (w/v) in 1 : 1 ratio. ATSBs were formulated by mixing each ASB with different concentrations of deltamethrin in the ratio of 9 : 1 to obtain final deltamethrin concentration of 0.003125–0.8 mg/10 mL ATSB. Cage bioassays were conducted with 50 mosquitoes for 24 h in order to evaluate the efficacy of each ATSB against the four strains of Ae. aegypti. The data were statistically analyzed using PASW software 19.0 program and 2-way ANOVA. Results. The ATSB formulations registered 8.33–97.44% mortality against AND-Aedes aegypti and 5.15–96.91% mortality against AND-Aedes aegypti-DL10 strains of Ae. aegypti, while GVD-Delhi strain registered 2.04–95.83% mortality and SHD-Delhi strain showed 5.10–97.96% mortality. The administration of 0.8 mg of deltamethrin within 10 mL of attractive toxic sugar bait (ATSB) has led to the maximum mortality rate in adult mosquitoes. Conclusions. The ATSBs formulated with guava juice-ASB and deltamethrin (9 : 1) showed toxin dose-dependent toxicity by all the four strains of Ae. aegypti. Most effective dosage was found as 0.8 mg deltamethrin/10 mL ATSB which imparted 96% to 98% mortality in adult mosquitoes. The investigations demonstrated the efficacy of deltamethrin-laced ATSB formulations against Ae. aegypti and highlighted the need for conduct of structured field trials and investigating the impact on disease vectors and nontarget organisms.